Penerapan Metode Fuzzy AHP dan Analytic Rubric dalam Penilaian Kinerja Karyawan (Studi Kasus pada PT. XYZ) - Erwin Setiawan (Universitas Kristen Maranatha, 2016)
PT. XYZ is acompany that distribute Pertamina products such as LPG, lubricants, and fuel. In the process of employee performance appraisal, PT. XYZ still has problems in determination of same weight rating in each department andalso the criteria, and subcriteria that are being used are still limited. This appraisal system has a negative impact like the reaction of some departments of the company (especially sales) about the current performance appraisal system. To resolve these problems, this research will design a new performance appraisal system using fuzzy AHP as a method for calculating the weight of each criteria and sub-criteria, thathave been established grounded on PPNo. 10 established 1979 and job description of each division of the Sales department and employee performance appraisal forms that already exist. Then Analytic Rubric will be applied to describe the degree ofquality scale that used by the company in the performance appraisal. By applying this methods and reference, it is expected to deliver assessment results that can represent the results of the employee's performance objectively based on the differences in duties and responsibilities of each division. So with the establishment of this new performance appraisal system, it can help the Human Resources HealthSafety and Environment - General Legal Affairs (HRS-LGA) in further data processing (evaluation).Keywords: Employee Performance Appraisal,PP no. 10 established 1979, fuzzy AHP, Analytic Rubric.